BARRIERS OF EYE CARE SERVICES FOR CATARACT PATIENTSIN AZAD JAMMU AND KASHMIR (Journal of Medical & Health Sciences Review, 2025)
Purpose: To find the barriers in eye care service for cataract patients in Azad Jammu and Kashmir.                         Design: Cross-sectional study.Method: 60 Cataract patients (30 males and 30 females) of Azad Kashmir. Log MAR Visual acuity chart was used to assess visual acuity. The confidence interval of 0.95 with α of 0.05 was taken. Refraction was done and appropriate glassesResult: The majority of people with school-level education have experienced cataracts. It may be due to a lack of awareness. 30/74 people with 1 year cataract have experienced decreased vision for 1 year. And 6/12 for 3 years (p=0.403). 40/74 & 12/74 people housewives and labourers, respectively, experienced cataracts for 1 year. And 6/12 for 3 years of people related to labouring (p=0.012). The majority of people living in rural areas were affected more, 58/74 for 1 year, 26/34 for 2 years, 10/ 12 for 3 years (p=0.947). Most people with surgery phobia are affected more as compared to those who don’t have issues with the surgery, 38/74 for 1 year, 22/34 for 2 years and 8/12 for 3 years affected by cataract (p=0.339).Conclusion: The majority of people with school-level education, living in rural areas, never examine their eyes due to surgery phobia and doing housework or labouring have experience.